Patients' goals, resources, and barriers to future change: A qualitative study of patient reflections at hospital discharge after myocardial infarction. (December 2016) - Fålun, Nina; Fridlund, Bengt; Schaufel, Margrethe A; Schei, Edvin; Norekvål, Tone M
Background: Myocardial infarction (MI) patients may find it challenging to adhere to lifestyle advice and medications. Understanding motivational factors and barriers to change is crucial. However, empirical evidence on patients' ability to effect lifestyle changes at the time of discharge is limited. Aim: The aim of this study was to identify at the time of hospital discharge the goals, resources, and barriers to future change in MI patients. Methods: We conducted a qualitative interview study with a purposive sample of 20 MI patients (eight women) in a cardiac department at a university hospital in Norway. All interviews were conducted before hospital discharge, transcribed verbatim, and analysed using qualitative content analysis. Findings: Three themes suggested that, at the time of discharge, patients' views of their MI were complex and diverse. Patients were motivated to change their lifestyle and contemplated taking their life in new directions, adopting a change of life perspective . Frequently, patients struggled to understand the context of living with an MI, manage symptoms, and understand the precipitating causes of MI. There were also patients who wanted to maintain their present lifestyle and live as normal as possible. They just wanted to keep going . Conclusions and implications: There is a need for a different approach to communicating with MI patients at the time of discharge. Person-centred care that allows personal narratives to emerge may enable health-care professionals to offer more individualised guidance to MI patients that will help them cope with the everyday challenges they experience after discharge.